2022
DOI: 10.3389/fnut.2021.772645
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Inoculation of Fresh or Frozen Rumen Fluid Distinguishes Contrasting Microbial Communities and Fermentation Induced by Increasing Forage to Concentrate Ratio

Abstract: In vitro rumen batch culture is a technology to simulate rumen fermentation by inoculating microorganisms from rumen fluids. Although inocula (INO) are commonly derived from fresh rumen fluids, frozen rumen fluids are also employed for the advantages of storing, transporting, and preserving rumen microorganisms. The effects of frozen INO on microbial fermentation and community may be interfered with by substrate type, which has not been reported. This study was designed to test whether rumen fluid treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We found similarities in the overall bacterial community estimated by the Bray-Curtis index between two fluid types. Ma et al [26] observed similar results when fresh and frozen rumen fluids were studied for microbial community profiling. It was expected that the DNA of the inactive or dead microorganisms were retained in the fermentation flask in our research.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We found similarities in the overall bacterial community estimated by the Bray-Curtis index between two fluid types. Ma et al [26] observed similar results when fresh and frozen rumen fluids were studied for microbial community profiling. It was expected that the DNA of the inactive or dead microorganisms were retained in the fermentation flask in our research.…”
Section: Discussionmentioning
confidence: 62%
“…The source of rumen fluid and replication of the in vivo conditions in in vitro fermentation are the key components to overcome the challenging steps involved in in vitro rumen fermentation. The source of rumen fluid can be from live animals fed production [24] or maintenance rations [7], rumen fluid from slaughterhouses [25], or frozen rumen fluid [26,27]. Henderson et al [28] reported that the core microbiome in vivo is conserved across geographical regions no matter the species or feed; however, the relative abundances of the microbes vary with the diet and the ruminant species.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, the frozen treatment without a cryoprotectant seemed to offer the most favorable solution for rank-ordering in the absence of fresh rumen fluid ( Garcia et al, 2021 ). Ma et al (2022 ) compared IV fermentations with fresh and frozen ruminal fluid and the DM digestion was 4 percentage units less for frozen than fresh inocula; however, when the concentrate: forage ratio was 1:4 the DM digestion was 10 percent units less than a 1:1 ratio. Gas production was reduced when frozen inocula were used through the rank order of 1:4 and 1:1 concentrate: forage remained the same.…”
Section: Yr Later: What Progress Has Been Made Since 1993?mentioning
confidence: 99%